Evaluation of Cytoprotective Effect of Silymarine, Rutin, and Catechin on Cyclophosphamide-Induced Toxicity on Brain, Heart, and Spleen in Mice - Parashar, Deepesh (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the present study was to evaluate the cytoprotective effect of silymarine (SIL), rutin (RUT), and catechin against cyclophosphamide (CYP)-induced toxicity. Materials and Methods: The protocol for the study includes a total of 36 balb c mice and divided into six equal groups. These groups were: Control, CYP (25 mg/kg b.w., i.p), CYP + Amifostine (AMF) (200 mg/kg b.w., i.p), CYP + SIL (100 mg/kg b.w., oral), CYP + RUT (50 mg/kg b.w., oral), and CYP + Catechin(40 mg/kg b.w., oral). AMF, SIL, RUT, and Catechin treatments were performed for 14 days, while CYP was given till 10th day of the study. Cytotoxicity was measured followed lipid peroxidation (LPO), antioxidant markers such as superoxide dismutase, reduced glutathione, catalase, and examined the histology of brain, heart, and spleen in all groups. Results: During CYP treatment, all three flavonoids increased the levels of antioxidant markers and reduced the level of LPO. The CYP toxicity in brain, heart, and spleen has been reduced by flavonoids coadministration which can be clearly seen in results of LPO, antioxidant markers, and also in results of histopathology. Conclusion: Our study demonstrated that SIL, RUT, and catechin reduce the toxic effect of CYP and these compounds may serve as a safe medicinal supplement during CYP chemotherapy in cancer treatment.